The Compassion of Christ in the Gospel of Mark: A Christological Study and Its Implications for Local Church Ministry - Dotulong, Steven Richard; Thomas, Art S.; Pinontoan, Denni H. R. (International Journal of Education, Information Technology, and Others, 2025)
This study aims to explore the compassion of Christ in the Gospel of Mark as a central aspect of Markan Christology and to trace its implications for local church ministry. In various pericopes of Mark, Jesus is portrayed not only as the one who suffers and redeems, but also as the Messiah who actively touches, heals, and restores the wounded and the marginalized. Using a qualitative approach and a library research method, this study analyzes key texts exegetically and interprets their theological and contextual significance. The findings indicate that Christ’s compassion is not merely an emotional or human response, but a manifestation of divine authority and a concrete expression of God’s saving mission. These insights call for a renewed ministry paradigm in the local church—one that is more compassionate, contextual, and transformative—so that the church may truly embody the face of Christ who cares deeply and acts redemptively in a broken world.